Extraction of Phenolic Compounds from Banana Inflorescence (Musa acuminata) Using Supercritical Carbon Dioxide (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Banana inflorescence from Musa acuminata, frequently seen as agricultural waste, is a substantial source of bioactive compounds such as polyphenols and flavonoids. Efficient extraction methods can unlock its potential for functional food. This study aims to evaluate the impact of ethanol as a co-solvent concentration on extract yield, total flavonoid content (TFC), and antioxidant activity. Banana inflorescence was dried using an oven at 60 °C for 4 hours, ground into a fine powder, and stored in vacuum-sealed containers at -20 °C. For maceration, 10 g of the powder was combined with 100 mL of ethanol, agitated for 24 hours, and the ethanol was subsequently evaporated. For supercritical carbon dioxide (scCO₂) extraction, 10 g of powder was extracted using 50% and 100% ethanol as co-solvents under four conditions: 60 °C, 40 MPa; 60 °C, 25 MPa; 40 °C, 40 MPa; and 40 °C, 25 MPa. Extract yield, TFC, and antioxidant activity were measured, with flavonoid content quantified as quercetin equivalents (QE) and antioxidant capacity evaluated using IC50 values. The maximum yield (4.80%) was achieved using scCO₂ extraction with 100% ethanol at 60 °C and 40 MPa, attributed to enhanced solubility at elevated temperature and pressure. TFC was consistently higher with scCO₂ than maceration, reaching 552.94±0.84 mg QE/g using 50% ethanol at 60 °C and 40 MPa due to improved CO₂ density. Antioxidant activity peaked scCO₂ extraction using 100% ethanol at 40 MPa and 40 °C yielding the lowest IC50 (7.97±0.68), indicating superior radical scavenging. These results highlight scCO₂ extraction’s efficacy in maximizing bioactive compounds recovery and antioxidant potential from the banana inflorescence.
Keywords: Antioxidants; Banana inflorescence; Ethanol; Flavonoids; Supercritical carbon dioxide